2021
DOI: 10.1149/1945-7111/ac334d
|View full text |Cite
|
Sign up to set email alerts
|

Lithium-Sulfur Batteries Based on Sulfurized Poly(acrylonitrile) Cathodes: impact of Electrode Density on Cell Performance

Abstract: Calendering of battery electrodes during the manufacturing process enhances the volumetric energy density by increasing the electrode density and has a substantial impact on the cell performance of Li-ion and post-Li-ion batteries. Herein, we present a detailed study on the influence of electrode density on the electrochemical performance of sulfurized poly(acrylonitrile) (SPAN) cathodes. A correlation of the density of the SPAN cathodes with electrode properties and cell performance by applying various chemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The calendering process is one critical step that determines the macroporous structure, electrolyte/sulfur ratio, mechanical properties, and bulk density and conductivity of the electrodes. [215][216][217][218][219][220][221][222][223][224] Some studies showed interesting results for calendered electrodes of LSBs.…”
Section: Calendering Of Lithium-sulfur Battery Electrodesmentioning
confidence: 99%
See 1 more Smart Citation
“…The calendering process is one critical step that determines the macroporous structure, electrolyte/sulfur ratio, mechanical properties, and bulk density and conductivity of the electrodes. [215][216][217][218][219][220][221][222][223][224] Some studies showed interesting results for calendered electrodes of LSBs.…”
Section: Calendering Of Lithium-sulfur Battery Electrodesmentioning
confidence: 99%
“…Niesen et al [ 222 ] developed sulfurized poly(acrylonitrile) cathode materials and made electrodes with 90 wt% active material content, with an areal loading of 2.7 mAh cm −2 . With increasing in density from 0.8 to 1.0 g cm −3 via calendering, no change can be seen in the cells' rate performance and the long‐term cycling test (which demonstrated a decay of ∼8% (0.05% per cycle) after 400 cycles).…”
Section: Calendering Of Lithium–sulfur Battery Electrodesmentioning
confidence: 99%
“…12 Sulfurized poly(acrylonitrile) (SPAN) as cathode active material unites various positive aspects, among these low capacity fading, resilient response to high currents and compatibility with carbonatebased electrolytes. [13][14][15][16][17][18][19][20] Especially the latter is an atypical characteristic for S-cathodes, as intermediates during charge and discharge (PSs) undergo parasitic side reactions with carbonates resulting in electrolyte and active material degradation. 21 The absence of similar degradation phenomena when combining SPAN with carbonate electrolytes and little to no aging through the polysulfide shuttle mechanism led to a controversial debate about the exact redox mechanism of SPAN in various M-SPAN batteries.…”
mentioning
confidence: 99%